ANALYSIS OF STRATEGIES FOR REVERSAL LOGISTICS: A CASE STUDY ON THE HAVAIANAS FLIP FLOPS IN SÃO PAULO (SP) AND JOÃO PESSOA (PB), BRAZIL - Barbosa, Karlla Vanessa de Camargo; Silingovski, Tatiane Magalhães; Teixeira, Alexandra Alcantara; Giovanni, Renato de; Almeida, Thomaz; Martins, Cristina Saddy; Uezu, Alexandre (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Advances in technology and marketing concepts have been contributing in reducing the life cycle of products and to their rapid discard. In the other hand, new sustainable strategies seek to close the product cycle in the market through reverse logistics. The present study aimed to examine the consumer’s willingness to return consumed products through two strategies for collecting, using Havaianas sandals as a case study: direct return or selective disposal. A total of 807 questionnaires were administered in two large Brazilian cities, João Pessoa (390) and São Paulo (417), and recycling cooperatives were visited. In total, about 80% reported using the sandal. In São Paulo city, among the almost 73% that were willing to return the sandals, 34% would do it without any financial encouragement. In João Pessoa, among the 85% that would return the sandals, about 43% would not need any encouragement. In São Paulo, the potential for selective collection (60%) is superior to direct voluntary return (40%), and in João Pessoa both strategies are equivalent. We concluded that: both direct voluntary return and selective devolution are viable strategies, but a pilot project seems to be necessary to better evaluate the different strategies; cooperatives of collectors of recyclable materials may be a good alternative as a collaboration to collect the urban solid waste; the shared responsibility between society, government and companies is helpful for closing the cycle of materials; and the reverse logistic may play an important role in the business competitiveness.